2013
DOI: 10.1108/ijpdlm-03-2012-0062
|View full text |Cite
|
Sign up to set email alerts
|

Key success factor analysis for e‐SCM project implementation and a case study in semiconductor manufacturers

Abstract: PurposeThe semiconductor market exceeded US$250 billion worldwide in 2010 and has had a double‐digit compound annual growth rate (CAGR) in the last 20 years. As it is located far upstream of the electronic product market, the semiconductor industry has suffered severely from the “bullwhip” effect. Therefore, effective e‐based supply chain management (e‐SCM) has become imperative for the efficient operation of semiconductor manufacturing (SM) companies. The purpose of this research is to define and analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…That is why Cullen and Taylor (2009) accentuate the criticality of having a quality information system at the managers' disposal. However, drawing from the study done by Hwang and Lu (2013), having IT capability is futile without the drive and support from the top management. Therefore, it is not surprising for CSF2 to be among the vital CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is why Cullen and Taylor (2009) accentuate the criticality of having a quality information system at the managers' disposal. However, drawing from the study done by Hwang and Lu (2013), having IT capability is futile without the drive and support from the top management. Therefore, it is not surprising for CSF2 to be among the vital CSF.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ngai et al (2004) and Hwang and Lu (2013), commitment from the top management is critical for incorporating IT elements and SCM operation. Ngai et al indicated that besides driving the use of IT in SCM operation, top management support can come from psychological and behavioural support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the supply chain of agricultural products has become a huge issue because the citizen increasingly concerned about the safety of the foods being is consumed. At present, the process of farming, distribution, transportation, and other activities are interested for consumers of agricultural products [1] [13] [37]. Further, consumer behavior as such involves issues related to public health, which is influenced by existing cases on contaminated products [8].…”
Section: Introductionmentioning
confidence: 99%
“…The high level of uncertainty around market demand and the long lead-times required by the manufacturing process mean that IC manufacturers seek effective and efficient logistics management capability as a means to maximise the utilisation of manufacturing equipment. Located in the centre of the IC industry value chain, the IC manufacturing companies also need to collaborate closely with their partners both up and down the value chain to achieve high performance throughout the entire supply chain (Hwang and Lu, 2013).…”
Section: Introductionmentioning
confidence: 99%